NmeSI Restriction-Modification System Identified by Representational Difference Analysis of a Hypervirulent Neisseria meningitidis Strain - Bart, Aldert (American Society for Microbiology, 2001)
Neisseria meningitidis is a gram-negative bacterium that may cause meningitis, sepsis, or both. The increase in the incidence of meningococcal disease in various countries in the past 2 decades is mainly due the genotypically related lineage III meningococci. The chromosomal DNA differences between lineage III strains and non-lineage III strains were identified using representational difference analysis. Thus, a 1.8-kb locus that is specific for lineage III meningococci was identified. The locus contains three open reading frames encoding the NmeSI restriction-modification system. The methyltransferase gene was cloned and expressed in Escherichia coli. Site AGTACT was found to be modified by the enzyme. In conclusion, lineage III strains differ from endemic strains by the presence of a specific restriction-modification system. This restriction-modification system may contribute to the clonal and hypervirulent character of lineage III strains by influencing horizontal gene transfer and transcription.